Factores de riesgo asociados a mortalidad en pacientes con enfermedad renal crónica terminal. Hospitales minsa categoría III-1, Trujillo - Perú - Concepción Zavaleta, Marcio José (2015)
Objetive: Determine the direct causes of mortality and risk factors associated with mortality in patients with end-stage renal disease (ERCT) in MINSA hospitals category III-1 of Trujillo during the period 2008-2013 Material and method: The study population consisted of 430 patients diagnosed with ERCT in Hospital Belen and Hospital Regional of Trujillo, during the period 2008-2013, of which 62 patients died. The case group and control group were 41 deceased patients and 123 alive patients respectively, with the same diagnosis in the same hospitals during the same period Results and conclusions: The main cause of direct mortality was cardiovascular, followed by infectious and metabolic. Advanced age, diabetes mellitus, inadequate control of blood pressure, hemodialysis less than 3 times per week, moderate-severe anemia and poor response to administration of erythropoietin and iron, were risk factors associated with mortality. The use of central venous catheter during the course of the disease was found to be protective factor. The male sex wasn’t risk factor and protective factor. Hemodialysis less than 3 times per week was the risk factor most associated with mortality